PERAN DAN TANGGUNGJAWAB BANK SYARIAH DAN NASABAH TERHADAP PENGELOLAAN RESIKO PEMBIAYAAN BERMASALAH - Satrio Abdillah; Zaianal Efendi Hasibuan (Adpertens: Jurnal Ekonomi dan Manajemen, 2025)
This article examines the responsibilities of customers and Islamic Banks in managing problematic financing. This research also examines the terms of facility agreements by different Islamic banks to analyze the handling of problematic financing by the banks. The researcher employs a qualitative methodology, thus this research is based on primary data analysis from interviews with representatives of Bank A to determine the mechanisms used by Bank A to recover problematic financing, as well as secondary data. Secondary data was obtained by reviewing the relevant provisions of facility agreements from three Islamic Banks in relation to default events and compensation, and collecting information from the Policy Documents and Guidelines of Islamic banks. The conclusion of this research reveals the responsibilities of customers and Islamic banks in managing and handling problematic financing, as well as examining the steps taken by Bank A to recover its problematic financing. This research is important in highlighting the obligations of customers regarding their financing and the treatment of Islamic banks in assisting and addressing problematic financing.